The characterization of recycled concrete aggregate as filter in removal of phosphorus - Adnan, Suraya Hani; Abd Roni, Norwardatun; Tuan Ismail, Tuan Noor Hasanah; Hamidon, Nuramidah (Penerbit UTHM, 2020)
Phosphorus (P) is one of the key nutrients that lead to eutrophication problem in surface water. However, the existing conventional wastewater treatment system to remove phosphorus is expensive and require a complex process. Therefore, a system using low cost and environmental friendly should be practiced to overcome this problem. Recycled concrete aggregate (RCA) used as a filter system emerged as an alternative technology for phosphorus removal. This can overcome the problem of construction site waste by converting the waste into something valuable products. Thus, this study aim to investigate the physical and chemical characteristic of RCA that influenced adsorption of P. RCA was analyzed using Scanning Electron Microscopy (SEM) and Energy-dispersive X-ray spectroscopy (EDX) testing to determine chemical composition. Results shows that RCA is highly contained with Aluminium, Calcium and Magnesium elements that enhanced the Phosphorus adsorption.